Pengaruh Peran Kader pada Pijat Akupresure terhadap Keberhasilan ASI Eksklusif - Eprina Intami; Matda Yunartha; Margareta Pratiwi; Devi Arista (Universitas Batanghari Jambi, 2022)
In order to reduce infant morbidity and mortality, UNICEF and WHO recommend that babies should be given breast milk for at least 6 months and continue until the baby is two years old. Thus mothers can maintain exclusive breastfeeding for 6 months, WHO recommends initiating breastfeeding within the first hour of life. This study aims to see the effect of acupressure massage on milk production. The method used in this study is quasi-experimental design. This research was conducted in the working area of Puskesmas Kebun Kopi Jambi City in January - December 2020. The number of samples in this study were 30 respondents of breastfeeding mothers divided into 2 groups, namely the intervention group and the control group. The results of this study was analyzed using T-test. Based on the research results, the p-value is 0.000 (p <0.05). This shows that there is an effect of acupressure massage performed by cadres on the milk production process. The results showed that the provision of acupressure massage can affect the production of breast milk so that the milk obtained increases and smoothly so that breastfeeding mothers do not have to worry about their ability to breastfeed for up to 6 months. Exclusive breastfeeding for 6 months is highly recommended so that acupressure massage can help mothers in increasing milk production during the breastfeeding process.